Synthesis of Ni and Zn Based Organic Frameworks as Photocatalyst - Dikmen, Merve; Özkan, Seher Fehime (Izmir Institute of Technology, 2019)
Nickel (Ni) and zinc (Zn) based organic frameworks were synthesized on the synthetic zeolite (5A and 13X), natural zeolite mineral clinoptilolite, -Alumina. Initially the zeolite surface was modified or seeded with metal organic framework (MOF). MOF-zeolite composite materials were characterized with XRD, SEM and ATR-IR to understand whether surface processes was achieved successfully or not. Additionally, band gap energies were evaluated to understand these composite materials were used as photocatalyst. Surface modification with APTES was not affect surface of the zeolites. In spite of that seeding created a layer on the surface of zeolite. Nickel based organic framework was coated onto the surface of modified 5A surface. Hydrothermal ZIF8 (ZIF8(1)) and solvothermal ZIF8 (ZIF8(2)) were synthesized successfully as MOF crystals. Besides ZIF8(2) was coated onto the surface of natural zeolite. Additionally, ZIF8/CuBTC sample were synthesized, seeded and coated onto the surface of natural zeolite. Band gap energies of the MOFs and composite materials were calculated with Tauc plot. Results showed that UV light can be used as light source for photocatalytic reactions of these photocatalysts. Also increasing photocatalyst amount increased dye degredation under UV light.

Nikel ve çinko temelli organic ağ yapıları, zeolit 5A ve 13X, doğal zeolite ve alüminyum oksit’in yüzey işlemleri ve doğrudan sentez ve kaplama metotları ile yapılan metal organik ağ yapıları ile zeolitlerin oluşturduğu birleşik maddeler araştırılmıştır. Bu maddeler yüzey işlemlerinin başarılı olup olmadığını anlayabilmek için XRD, SEM ve ATR-IR ile analiz edilmiştir. Ayrıca bu birleşik maddelerin fotokatalizör olarak kullanılabileceği bant aralığı enerjileri incelenerek anlaşılmıştır. Yüzey modifikasyon işlemlerinden APTES isimli kimyasal ile yapılanın zeolite yüzeyine bir etkisi görülmemiştir. Buna karşın MOF kaplama işlemini kolaylaştırması için yapılan tutunma yüzeyi oluşturma işlemi başarı ile sonuçlanmıştır. Nikel temelli metal organic ağ yapısı yüzeyine modifikasyon işlemi uygulanmış zeolite 5A’nın yüzeyine başarı ile kaplanmıştır. ZIF8 isimli metal organic ağ yapısı iki farklı metot ile sentezlenmiş olup sentez sırasında çözücü olarak metil alkol kullanılan ürün ayrıca doğal zeolite üzerine de kaplanmıştır. Kaplama işlemi başarı ile gerçekleştirilmiştir. Buna ek olarak, ZIF8 ve bakır içeren metal organic ağ yapısı kompozit ürün olarak sentezlenmiş olup, bu ürün doğal zeolitin üzerine de sentezlenmiştir. Bu fotokatalizörlerin bant aralığı enerjileri incelenmiş olup UV ışık kaynağı ile fotokataliz reaksiyonlarının gerçekleştirilebileceği görülmüştür. Ayrıca yapılan UV ışığı kaynaklı deneyler sonucunda artan fotokatalizör miktarının solüsyondaki Rhodamine-B isimli boyayı bozundurduğu gözlemlenmiştir
Fotokatalizör Olarak Ni ve Zn Temelli Organik Ağ Yapılarının Sentezi
Thesis (Master)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2019
Includes bibliographical references (leaves: 46-48)
Text in English; Abstract: Turkish and English
Keywords: Natural zeolites; Clinoptilolite; Metal organic frameworks; Composite materials